Coexistence of Crohn's disease and systemic lupus erythematosus: a case report and literature review. Issue 9 (September 2020) - Jin, Xiaorong; Wang, Gui; Xu, Xiaohua; Bai, Yunjing; An, Ran; Jiang, Dexun
Abstract : Lupus enteritis and Crohn's disease are two common immune diseases involving the gastrointestinal tract. There are many similar clinical manifestations, therefore it is very difficult to distinguish between them. The digestive system is involved anywhere from 8 to 40% of patients with systemic lupus erythematosus (SLE) and up to 53% of these go on to develop lupus enteritis. In patients with Crohn's disease, 6–40% were presented with oral mucosa ulceration, nodular erythema of skin, arthritis, eye disease and other extraintestinal manifestations. The concomitant of Crohn's disease and SLE is extremely rare; however, here we described a case of concomitant Crohn's disease and SLE characterized by recurrent intestinal obstruction. A systematic literature review of lupus concomitant with Crohn's disease was then conducted.